Conceptual Approaches to Training Specialists Using Multimedia Technologies - Shchyrbul, Oleksandr; Babalich, Viktoriya; Mishyn, Sergii; Novikova, Viktoriia; Zinchenko, Lina; Haidamashko, Iryna; Kuchai, Oleksandr (My University, 2022)
Modernization of the educational sector requires globalization, democratization, and the transition to an information technology society. The main goal of education at the present stage is to solve the problem of ensuring the priority of the development of education and science. In modern conditions, the quality of training of qualified specialists is becoming particularly relevant. The great role of teacher education is emphasized by its main goal, which is to train specialists who can ensure the versatile and innovative development of a person as a person and the highest value of society, its mental, physical and aesthetic abilities, high moral qualities, and, consequently, the enrichment on this basis of the intellectual, creative and cultural potential of the people. Among the strategic tasks of modernizing higher education is to ensure informatization of the educational process and access to International Information Systems. The essence of the concept of multimedia is clarified. In the context of media education, multimedia lists a number of functions: informational, interpretive, cultural, entertainment, and educational. The need to meet the needs outlined in the article in the conditions of informatization of the educational process requires the teacher to have knowledge and skills in the field of multimedia pedagogical technologies, knowledge of advanced methods and means of modern science. It is considered what relevant concepts of media education have been developed and are being developed in Ukraine and form an important basis for the modernization of education, which will contribute to the construction of an information society in the country and the formation of civil society. Distance learning is considered – the most democratic form of education that allows broad segments of society to get an education. Distance learning methods are used in higher education institutions, in schooleducation, in the system of advanced training of teachers, in the system of training managerial personnel.
Keywords: multimedia technologies; conceptual approaches; training of specialists; informatization of the educational process; concepts of media education; modernization of education; information society